Minimally invasive thoracoscopic surgery with laparoscopic assistance approaches in diaphragmatic eventration management - Panko, Siarhei; Karpitski, Aliaksandr; Zhurbenko, Gennadij; Shestiuk, Andrej; Boufalik, Rotislav; Vakulich, Denis; Ignatjuk, Alaksandr (Medical Studies/Studia Medyczne, 2017)
Introduction : Thoracoscopic plication is an effective treatment for diaphragmatic eventration, but the procedure has some disadvantages such as inadvertent abdominal organ injuries or superficial sutures that are not strong enough. Aim of the research : In this study, we devised and tested the method of diaphragm plication through simultaneous laparoscopic- and thoracoscopic-assisted left mini-thoracotomy. Material and methods : During the period between October 2012 and March 2014 there were four patients operated on for left-sided diaphragmatic paralysis. The average age was 52.3 ±17.8 years. The preoperative examination included a routine laboratory study, spirometry, plain chest radiograph, and computed tomographic scan of the chest. The initial part of the surgery was a two-port laparoscopy to remove the adhesions between the abdominal viscera and the abdominal segment of the diaphragm using bipolar electrocautery. After that, video-assisted thoracoscopic surgery plication of the diaphragm was performed via anterior mini thoracotomy. Results : The mean operation time was 58 ±11 min, and the mean hospital stay was 9.0 ±2.1 days. All of the patients demonstrated good postoperative recovery. The descending distance of the diaphragm after the surgery ranged from two to four intercostal spaces, which was confirmed with plain chest X-ray. The follow-up ranged from 20 to 38 months and showed no recurrence of diaphragm elevation symptoms. Conclusions : Simultaneous thoraco- and laparoscopic assisted mini-thoracotomy surgery for diaphragm plication is a safe procedure with strong positive clinical effect, and it can serve as an alternative to conventional thoracoscopic approaches especially in patients with high risk of inadvertent abdominal organ injuries.